Comparison Between Central Corneal Thickness Measurements Obtained with Orbscan II Topographer and Ultrasonic Pachymeter - Sharif Hashmani, Irfan Shafiq (Pakistan Journal of Ophthalmology, 2007)
Purpose: To compare the central corneal thickness measurements obtained with Orbscan II scanning slit topographer and ultrasonic pachymeter in eyes undergoing corneal refractive surgery. Material and Methods: This non-interventional, observational comparative study was conducted in Hashmanis Eye Hospital Karachi. A total of 108 eyes evaluated for central corneal thickness measurement with Orbscan II scanning slit topographer and ultrasonic pachymeter that had undergone corneal refractive surgeries (LASIK, LASEK, PRK). The average age of the patients was 29.85 years. Result: The mean central corneal thickness (CCT) was 537.44?m standard deviation (SD) ±27.31?m standard error mean (SEM) ±2.63?m with Orbscan II scanning slit topographer and mean CCT 542.04 ?m SD ±26.35?m and SEM ±2.54?m with ultrasonic pachymeter (P = 0.007). Conclusion: The mean Central corneal thickness (CCT) from both devices was found not statistically significantly different from each other.